School culture as a mediator in the link between leadership and school effectiveness - Alanoglu, Muslim; Karabatak, Songul (Routledge Journals, Taylor & Francis Ltd, 2025)
This study examines the impact of transformational and servant leadership on school effectiveness by considering the role of school culture. A cross-sectional research design utilizing structural equation modeling was employed to analyze data collected from 471 teachers in T & uuml;rkiye. The results indicate that transformational leadership positively affects school effectiveness, while no direct effect was observed for servant leadership. However, the findings highlight the crucial mediating role of school culture in fostering effective schools for both transformational and servant leadership. Building upon these findings, the subsequent discussion explores how leadership shapes the development of school culture and how this culture, in turn, impacts school effectiveness. The insights gained from this research provide compelling evidence that the leadership style embraced and cultivated by school principals is crucial for the effective functioning of schools and that cultivating school culture is essential in achieving this objective.
Keywords: Transformational leadership; servant leadership; school culture; school effectiveness